2023
DOI: 10.3390/microorganisms11071836
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Arbuscular Mycorrhizal Fungi (AMF) Diversity in Light and Moderate Fire Sites in Taiga Forests, Northeast China

Abstract: Forest fires are an important disturbance factor in forest ecosystems, and obviously change the soil environment. Arbuscular mycorrhizal fungi, as a medium and bridge between vegetation and soil, play a crucial role in mediating plant nutrient uptake and regulating the productivity, stability, and succession of vegetation–soil systems. To investigate the effects of forest fires on the community structure and diversity of arbuscular mycorrhizal fungi in cold-temperate Larix gmelinii forests, we collected soils … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…On the contrary, fungi are very sensitive to fire, and their diversity usually decreases after fire [57]. However, Cheng et al found that the relative abundance of arbuscular mycorrhizal fungi recovered to pre-fire levels following high intensity fires disturbance (p > 0.05) [58].…”
Section: State Of the Artmentioning
confidence: 99%
“…On the contrary, fungi are very sensitive to fire, and their diversity usually decreases after fire [57]. However, Cheng et al found that the relative abundance of arbuscular mycorrhizal fungi recovered to pre-fire levels following high intensity fires disturbance (p > 0.05) [58].…”
Section: State Of the Artmentioning
confidence: 99%
“…This study area is located in Huzhong National Nature Reserve, which is the northernmost part of Daxing'anling region in Heilongjiang Province (51 1). The site follows a cold-temperate continental monsoon climate, with a large diurnal temperature change and an average annual temperature of −5.3 • C. The winter season is long, with a frost-free period of around 80 days, and the summer season is shorter, with a duration of no more than 30 days [22]. The topography is high in the east and low in the west, with an elevation of 847-974 m. The region has a uniform vegetation composition, mainly including Larix gmelinii, Pinussylvestris var.…”
Section: Overview Of the Study Areamentioning
confidence: 99%
“…After thorough mixing and removal of debris and rhizomes, the samples were sieved through a 2 mm sieve and stored in a cold place for further use. Part of the samples was utilized for soil bacterial DNA extraction, whereas the remainder was dedicated to determining soil physical and chemical properties; refer to previous literature for specific measurements [36].…”
Section: Sample Plotmentioning
confidence: 99%
“…The physicochemical characteristics of the soils of the burnt site under different disturbance intensities have been described before [36]; the physicochemical properties of the soil are shown in Supplementary Table S1.…”
Section: Differences In Physicochemical Properties Of Fire-burnt Site...mentioning
confidence: 99%